2002
DOI: 10.2355/isijinternational.42.248
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Molten Steel by the Air Permeated through a Refractory Tube.

Abstract: Refractory tubes such as a shrouding nozzle and a submerged entry nozzle are employed for molten steel transferring from a ladle to a tundish, and a tundish to a mold, respectively, to prevent molten steel from being oxidized. When the cross-sectional area in the molten steel flow channel is suddenly contracted and subsequently enlarged, a negative pressure is generated at the area. Thereby air is permeated into the molten steel flow through the refractory tube and oxidizes the molten steel.The permeability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 3 publications
1
12
0
Order By: Relevance
“…This rate will build up 1.1 mm thickness of clogging per hour on the entire SEN wall, assuming that 50% of the inclusions attach to the walls [40] and that the clog consists of 50% alumina and 50% steel [41]. This represents up to 30% of the typical clogging rate observed in commercial operations [26]. Note that the aspirated gas flow rate (Equation (42)) increases with the cube of the gap size, so large gaps will cause severe clogging and quality problems very quickly.…”
Section: Estimation Of Air Aspiration Reoxidation and Transient Clomentioning
confidence: 99%
See 1 more Smart Citation
“…This rate will build up 1.1 mm thickness of clogging per hour on the entire SEN wall, assuming that 50% of the inclusions attach to the walls [40] and that the clog consists of 50% alumina and 50% steel [41]. This represents up to 30% of the typical clogging rate observed in commercial operations [26]. Note that the aspirated gas flow rate (Equation (42)) increases with the cube of the gap size, so large gaps will cause severe clogging and quality problems very quickly.…”
Section: Estimation Of Air Aspiration Reoxidation and Transient Clomentioning
confidence: 99%
“…Another model used a Smoothed Particle Hydrodynamics (SPH) method to predict the amount of oxides in cast ingots during filling, based on the surface area of metal exposed to the air [25]. A study of reoxidation due to air permeation through the SEN refractory wall [26] concluded that this source of oxides is not enough to be fully responsible for nozzle clogging. However, the contribution of aspirated air through possible cracks or gaps in the refractory was not considered.…”
Section: Previous Modelsmentioning
confidence: 99%
“…It was assumed that the permeability of the SEN refractory to CO gas was sufficiently high that CO gas flowing through refractory pores did not cause any pressure drop. Laboratory [28] and plant [4] scale investigations on the permeability of SEN refractories have shown that SEN permeability does not play a significant role in clogging. Therefore, the above assumption of a large permeability of the SEN refractory appears reasonable.…”
Section: A Validation Of the Modelmentioning
confidence: 99%
“…The decrease in pressure can cause air to be sucked through cracks, joints and porous refractory of the submerged entry nozzle (SEN), making re‐oxidation of steel possible 1–4. On the other hand, according to the measurements made by Suzuki et al 5 remarkable re‐oxidation of steel cannot be attributed to air sucked through refractory.…”
Section: Introductionmentioning
confidence: 99%